2018
DOI: 10.1002/ams2.334
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of patients with hypermagnesemia who underwent emergency hemodialysis

Abstract: AimThis study aimed to clarify the characteristics of patients who presented with severe hypermagnesemia and subsequently underwent emergency hemodialysis.MethodsWe investigated the age, gender, complications, clinical symptoms, causal drugs, electrocardiogram findings, and laboratory data of 15 patients.ResultsMagnesium oxide had been administered in all cases and 14 patients were over 65 years old. The male : female ratio was 6:9. Chief complaints included a disturbance of consciousness, hypotension, bradyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…High CKD, greater age, and long-term use of magnesium oxide were shown to be risk factors for hypermagnesemia. (3,(5)(6)(7)(8)(9)(10) Most of these studies, however, were case reports or studies of certain groups, including elderly patients, children, and patients undergoing hemodialysis. The results of the present retrospective cohort study showed that reduced renal function was the most important risk factor for hypermagnesemia and high serum magnesium concentration in patients taking magnesium oxide for functional constipation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High CKD, greater age, and long-term use of magnesium oxide were shown to be risk factors for hypermagnesemia. (3,(5)(6)(7)(8)(9)(10) Most of these studies, however, were case reports or studies of certain groups, including elderly patients, children, and patients undergoing hemodialysis. The results of the present retrospective cohort study showed that reduced renal function was the most important risk factor for hypermagnesemia and high serum magnesium concentration in patients taking magnesium oxide for functional constipation.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Prolonged treatment with magnesium oxide, however, may induce hypermagnesemia. (4)(5)(6)(7)(8)(9) Serum magnesium concentrations >5.0 mg/dl have been associated with nausea, headache, light-headedness, and cutaneous flushing, whereas levels above 12 mg/dl have been associated with respiratory failure, complete heart blockage, and cardiac arrest. (10) Recently, the Japanese Ministry of Health, Labour and Welfare recommended that serum magnesium concentrations be measured periodically in geriatric patients and in patients administered magnesium oxide for prolonged periods of time (http://www.pmda.…”
mentioning
confidence: 99%
“…Excessive intake of supplemental Mg 2+ can result in adverse effects, especially in impaired renal function. Serum concentrations >8 mmol/L cause drowsiness, vasodilation, slowing of atrioventricular conduction, and hypotension [ 126 , 127 , 128 ].…”
Section: Mgd Groups At Risk Replacement Therapy and Preventionmentioning
confidence: 99%
“…Henle's loop has the capacity to completely reject Mg reabsorption under conditions of hypermagnesemia, and hence, a maximal renal excretion of more than 6 g/day (500 mEq/day) can occur [4]. Renal dysfunction thus leads to hypermagnesemia, and eGFR <30 ml/min/1.73 m 2 is also associated with elevated risk of hypermagnesemia [7]. Mg regulation mainly occurs in the small intestine, particularly in the proximal portions [7], and its mechanism of regulation is mainly through passive diffusion [4].…”
Section: Discussionmentioning
confidence: 99%
“…Renal dysfunction thus leads to hypermagnesemia, and eGFR <30 ml/min/1.73 m 2 is also associated with elevated risk of hypermagnesemia [7]. Mg regulation mainly occurs in the small intestine, particularly in the proximal portions [7], and its mechanism of regulation is mainly through passive diffusion [4]. Also, an elevation in Mg concentration is much more likely in the presence of gastrointestinal disorders (active gastric ulcer disease, gastritis, colitis) that can enhance Mg absorption [1].…”
Section: Discussionmentioning
confidence: 99%